POSITIONAL MEASUREMENTS OF THE METEOR TV IMAGES - Gorbanev, Yu. M.; Kimakovsky, S. R.; Knyazkova, E. F. (Одеські астрономічні публікації, 2009)
We discuss the methods and software which is used for processing of the meteor TV images. Methods are based on the principles of the aperture CCD photometry. Software enables one to make processing of the observational material that was secured using TV methods with telescopic systems (field of view less that 1 angular degree), as well as with astrocameras of the wide field of view (field of view less 2-4 angular degrees, and even more than 50 degrees). We also elaborated method that allows one to identify operatively and to measure automatically rectangular coordinates within the image frame, as well as to calculate equatorial coordinates of the object using the Turner method and compiled stellar catalogues. This method was tested with observational material obtained with the help of TV meteor patrol within the period from 2003 to 2010 at Kryzhanovka station that belongs to Astronomical Observatory of Odessa National University. We performed an analysis of accuracy determination of the stellar images measurements. Software was tested in order to use it for the comet observations.